A unified port-Hamiltonian approach for modelling and stabilizing control of engineering systems - Hoang, Ha Ngoc; Le, Quyen Phuong; Nguyen, Chi Thuan (Vietnam Journal of Science and Technology, 2021)
This work deals with systems whose dynamics are aﬃne in the control input. Such dynamics are considered to be significantly diﬀerentially expressed in a canonical form, namely the quadratic (pseudo) port-Hamiltonian representation, in order to explore further some structural properties usable for the tracking-error passivity-based control design. Diﬀerent kinds of linear and nonlinear engineering systems including an open isothermal homogeneous system and a continuous biochemical fermenter are used to illustrate the approach.